Measles - Griffin, Diane E. (Henry Stewart Talks, 2020)
Introduction to measles as a systemic rash disease, Measles virus and replication, Virus proteins for cell entry, fusion and formation of multinucleated giant cells, Transmission, systemic spread, immune response, complications and clearance, Vaccine characteristics, efficacy and coverage, Measles epidemiology, Problems with control